PERAN KOMUNIKASI PERSUASIF DALAM MENGEMBANGKAN UMKM KELOMPOK WANITA TANI DI SINDU MAKMUR, SINDUHARJO, JATIPURO, KARANGANYAR - Astuti Itasari, Andri; Sihabuddin, Sihabuddin (LPPM Universitas Bina Bangsa, 2024)
Persuasive communication plays a significant role in the development of MSMEs, particularly in enhancing the effectiveness of product marketing. The MSME Sindu Makmur, managed by the Women Farmers Group (KWT), produces products such as mocaf flour and traditional herbal medicine in powder form. These products have high market potential if developed to their fullest extent. However, the KWT faces various challenges in effectively marketing these products. Through this community service program, the team aims to provide counseling, training, and development of persuasive communication skills to the members of KWT Sindu Makmur. This program is designed to equip them with effective communication techniques that can help attract consumer interest and increase product sales. By understanding and applying persuasive communication, it is expected that KWT Sindu Makmur can overcome marketing challenges and maximize the market potential of their products. The expected outcomes of this activity are that the partners will be able to understand and practice persuasive communication effectively. This improvement is expected to have a positive impact on the promotion and sales of Sindu Makmur MSME products